A robust DEA‐centric location‐based decision support system for expanding Recreovía hubs in the city of Bogotá (Colombia). (13th July 2018) - Abolghasem, Sepideh; Solano, Felipe; Bedoya, Claudia D.; Navas, Lina P.; Ríos, Ana Paola; Pinzón, Edwin A.; Medaglia, Andrés L.; Sarmiento, Olga L.
Abstract: Multisectorial community programs to promote healthy living in public spaces are crucial for building a "culture of health" and could contribute to achieving the specific 2030 agendas of sustainable development goals, including reduction of inequalities; provision of inclusive, safe, resilient, and sustainable cities; and promotion of just, peaceful, and inclusive societies. In this context, the Recreovía program of Bogotá (Colombia) provides physical activity classes in parks mainly for vulnerable communities. We address the challenge of efficiently locating new Recreovía hubs through a novel robust data envelopment analysis (DEA) centric location‐based decision support system (DSS) that helps the District Institute of Sports and Recreation of Bogotá (IDRD) to locate the best hubs to expand the Recreovía program throughout the city. The tool is applied to analyze different scenarios including one that was implemented in Bogotá and yielded an improvement of 28% in compound monthly growth rate of the average attendance to the hubs.